A Study On Effectiveness Of Competency Mapping Through Training AndDevelopment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s corporate world, many companies and organization are increasingly focusing on human capital as a competitive advantage in rapidly changing environment. Many successful companies realize that their employees are their greatest asset. Therefore, companies are increasingly investing in educating their own employees so that they can grow and change within the company and make it more profitable.The range of training opportunities varies considerable from company to company so, when researching potential employers, it is important for job seekers who  care  about  this  to  investigate  the  level  and  type  of  training  provided  to employees.  After  employees  have  been  selected  for  various  positions  in  an organization,  training  them  for specific  tasks  to  which  they  have  been  assigned assumes greater importance.     This study suggests the organization to implement more modern training methodologies, then to provide practical training to the employees and to provide specific learning assignments or projects for participants to improve on their competency gap.